Synthesis of V-Ti-Cr alloys by aluminothermy co-reduction of its oxides - Sanjay Kumar (Processing and Application of Ceramics, 2011)
Synthesis of V-Ti-Cr solid solution alloy by co-reduction of V2O5, Cr2O3 and TiO2 with aluminium in an open bomb reactor was investigated. The reduction of V2O5 and Cr2O3 was highly exothermic while reduction of TiO2 was not sufficiently exothermic for self-sustaining reaction. A range of composition of V2O5, Cr2O3 and TiO2 mixture was chosen to make overall process sufficiently exothermic to sustain the reaction in a controlled manner. After the co-reduction, V-Ti-Cr-Al solid solution was obtained. As-obtained solid solution was refined by electron beam melting (EB) to remove the aluminium and residual oxygen. EB melted V-Ti-Cr thus obtained contains substantially less amount of aluminium (~0.081%.) Throughout the synthesis process the prepared products were analyzed using scanning electron microscope (SEM), energy dispersive X-ray fluorescence (EDAX), chemical analysis, gravimetric analysis and X-ray diffraction.